SCREENING FOR AFLATOXIGENIC FUNGI IN STORED AND OPEN MARKET GRAINS IN POTISKUM, NORTHEAST NIGERIA - Gide, Suleiman; Abdulkarim, Sabo Mohammed; Danjuma, Lawal (FUDMA JOURNAL OF SCIENCES, 2025)
Fungal and aflatoxin contaminations of grains pose a significant risk to human health as well as animal health hence the need to screen for the presence of aflatoxigenic fungi in grains. Isolation and identification of fungi associated with grains was carried out on 50 samples including rice, millet, wheat, sorghum, barley, maize and sesame obtained from local grain markets and stores in Potiskum. Potato dextrose agar (PDA) and Neutral red desiccated coconut agar (NRCDA) were used for isolation and direct visual determination of aflatoxigenic fungi respectively. Fungal isolates were then screened qualitatively for aflatoxin B1 production by inoculating a pinch of mycelia onto the centre of NRDCA plates. Seven fungi species belonging to the four genera were identified. These include Rhizoctonia, Botrytis sp, Fusarium, Aspergillus flavus, Aspergillus paraciticus, Aspergillus fumigatus and Aspergillus niger. The most predominant fungal genus isolated from stored and open grains markets was Aspergillus. Aspergillus flavus had the highest detection frequency in both stored grain (4, 28.57%) and open grains (2, 40.0%). A. flavus isolated from stored sorghum, maize and sesame exhibited very bright blue fluorescence followed by A. parasiticus isolated from stored red sorghum which exhibited moderate bluish white fluorescence. The aflatoxigenic Aspergillus species 31.58% (n=6) were significantly correlated with qualitative results obtained from NRCDA plates. Isolates from samples with positive results for aflatoxin B1 detection and having blue fluorescence showed amplification of two target genes. Similarly, 14.29% (n=2) of the non-aflatoxigenic isolates were negative for the two genes.